The dragons of autism : autism as a source of wisdom - Holland, Olga, 1957- (Jessica Kingsley Publishers, 2003)
When a child is diagnosed with autism, the parents' initial reaction is often one of hopelessness and fear that nothing can be done. Olga Holland experienced these emotions when her son Billy was diagnosed, but instead of giving up hope, she developed strategies to contain Billy's autistic behaviors, and since then she and her family have come to view autism as a blessing, not a curse. In this book Olga describes the real-world strategies that have made Billy better able to cope with life, reducing his meltdowns and helping him to accept variety and change, and she explains how working with au.
Includes index.
Keywords: Autistic children -- Family relationships.; Parents of autistic children.; Autism in children.; Autistic Disorder; Enfants autistes -- Relations familiales.; Parents d'enfants autistes.; Autisme infantile.; MEDICAL -- Pediatrics.; HEALTH & FITNESS -- Children's Health.; Autism in children; Autistic children -- Family relationships; Parents of autistic children